Analisis Program Pemutihan PKB, Pembebasan BBNKB Dan Sosialisasi Pajak Dalam Upaya Meningkatkan Penerimaan PKB - Aeni, Silvia; Sudarma, Ade; Tanjung, Hendra (Universitas Muhammadiyah Metro, 2023)
This study aims to describe and analyze the application of the motor vehicle tax bleaching program, name change duty, and tax socialization in increasing motor vehicle tax revenue (PKB) at SAMSAT Sukabumi I Cibadak Regency. Where motor vehicle tax and name return duty are the largest tax contributions to Regional Vehicle Tax revenue. This research uses a qualitative approach with primary data, interviews and secondary data in the form of data collection techniques and supported by observation and documentation methods. The decline in the realization of motor vehicle tax revenue and motor vehicle name return duty is due to the lack of public awareness in paying taxes. The results of the analysis conducted by researchers related to the implementation of the motor vehicle tax bleaching program, name reversal duties, socialization are quite good.